Depression in Adolescents with Asperger’s Syndrome: Long-Term Outcome - I. Nicolau; C. Voinea; L. Mateescu (European Psychiatry, 2022)
Introduction Asperger Syndrome (AS) exhibits a particular set of difficulties, the foremost of them being the impairment in social interaction. Furthermore, adolescence by itself is a period burdened with many social challenges and distress. The attempt to adjust to them while having AS is much harder, thus it may constitute the premise for the onset of internalizing symptomatology, in particular depression.